ICP6 Prevents RIP1 Activation to Hinder Necroptosis Signaling - Hu, Hong; Wu, Guoxiang; Shu, Zhaoqian; Yu, Dandan; Nan, Ning; Yuan, Feiyang; Liu, Xiaoyan; Wang, Huayi (Frontiers in Cell and Developmental Biology, 2020)
Necroptosis is a type of programmed necrosis which depends on the activation of receptor-interacting protein kinase 3 (RIP3). Herpes simplex virus type 1 (HSV-1) is known to block necroptosis by the viral protein ICP6 in human cells, but its specific inhibitory mechanism is not fully understood. Here we reported that ICP6 could promote rather than suppress the formation of necrosome, the necroptosis signaling complex containing RIP3 and upstream regulator receptor-interacting protein kinase 1 (RIP1), but blocked RIP3 activation. Moreover, ICP6 could reduce the necroptosis-specific auto-phosphorylation of RIP1 regardless of the presence of RIP3. These results indicate that ICP6 block necroptosis through preventing RIP1 activation dependent signal transduction in necrosome.